Scabies mimicking graft versus host disease in a hematopoietic cell transplant recipient - Dongsub Kim; Soo-Han Choi; Dong Youn Lee; Juyoun Kim; Eunjoo Cho; Keon Hee Yoo; Hong Hoe Koo; Yae-Jean Kim (Korean Pediatric Society, 2018)
Scabies is a highly contagious skin infestation caused by the mite, Sarcoptes scabiei var. hominis. Complex responses to scabies mites in the innate, humoral, and cellular immune systems can cause skin inflammation and pruritus. Diagnosis can be challenging because scabies resembles other common skin conditions. We report the first Korean case of scabies in a hematopoietic cell transplant (HCT) recipient, initially suspected of skin graft versus host disease (GVHD). A T-cell acute lymphocytic leukemia patient underwent a sibling-matched allogeneic HCT and developed pruritus after cell engraftment. Treatment for GVHD did not improve the symptoms. He was diagnosed with scabies 30 days after the onset of symptoms.